2021
DOI: 10.1016/j.aucc.2020.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Australian College of Critical Care Nurses and Australasian College for Infection Prevention and Control position statement on facilitating next-of-kin presence for patients dying from coronavirus disease 2019 (COVID-19) in the intensive care unit

Abstract: The coronavirus disease 2019 (COVID-19) pandemic is challenging healthcare systems worldwide, none more so than critical and intensive care settings. Significant attention has been paid to the capacity of Australian intensive care unit (ICUs) to respond to a COVID-19 surge, particularly in relation to beds, ventilators, staffing, personal protective equipment, and unparalleled increase in deaths in ICUs associated with COVID-19 seen internationally. While death is not uncommon in critical care, the internation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…In response, a suite of public health measures, such as restricting the free movement of people and limiting crowd sizes in the community, was implemented in an attempt to control the pandemic and minimize the risk of outbreaks (Parodi & Liu, 2020). In hospitals, infection prevention and control (IPC) measures have resulted in widespread use of personal protective equipment, isolation of patients with suspected or confirmed COVID‐19, monitoring of staff and visitors for symptoms of COVID‐19, and significant restrictions to visitors wanting to visit hospitalized patients (Bloomer & Bouchoucha, 2020; WHO, 2020b). A recent media report also describes how even when a patient was dying, visitors were banned (Hafner, 2020).…”
mentioning
confidence: 99%
“…In response, a suite of public health measures, such as restricting the free movement of people and limiting crowd sizes in the community, was implemented in an attempt to control the pandemic and minimize the risk of outbreaks (Parodi & Liu, 2020). In hospitals, infection prevention and control (IPC) measures have resulted in widespread use of personal protective equipment, isolation of patients with suspected or confirmed COVID‐19, monitoring of staff and visitors for symptoms of COVID‐19, and significant restrictions to visitors wanting to visit hospitalized patients (Bloomer & Bouchoucha, 2020; WHO, 2020b). A recent media report also describes how even when a patient was dying, visitors were banned (Hafner, 2020).…”
mentioning
confidence: 99%
“…69 Limitations in family access to ICUs are still common even though some institutions are allowing visits to some extent, especially when dealing with end-of-life situations. 70 , 71 This aspect appears to be burdensome for all the people participating to ICU care: patients may experience depression and anxiety; relatives do not have the chance to physically interact with their loved ones and personally observe and assist in treatment and caring process. The effect of these limitations may increase the development of anxiety, post-traumatic stress and complicated grief for families ( Figure 3 ).…”
Section: Palliative Care and Covid-19mentioning
confidence: 99%
“…The same results were also reported in Melissa et al study of infection control in healthcare providers. They concluded that by providing infection prevention and control measures for emergency care workers, they can take care of the patients as best as they can although the implementation of these guidelines require a uni ed approach [16]…”
Section: Preventionmentioning
confidence: 99%